Enhancing monellin production in Pichia pastoris fed-batch fermentation through an efficient on-line methanol/sorbitol co-feeding strategy. (1st October 2022) - Jia, Luqiang; Li, Teng; Yang, Zhenquan; Li, Tianyi; Ding, Jian
Abstract: Methanol is the sole inducer for driving recombinant protein expression in P. pastoris fed-batch fermentation. However, when adopting methanol-only feeding and controlling its concentration at the optimal level (5–10 g/L) would decrease dissolved oxygen concentration (DO) down to limitation conditions due to its high combustion enthalpy, leading to the severe accumulations of formaldehyde and a limited recombinant protein expression. To solve these problems, with help of the lower combustion enthalpy of sorbitol, an efficient on-line methanol/sorbitol co-feeding strategy was proposed, using monellin production as a prototype. The scheme of this strategy was that the feeding of methanol was controlled by ON-OFF control mode to ensure methanol induction strength via controlling its concentration around 5–10 g/L, while the co-feeding of sorbitol was determined by an improved DO-stat mode to repress the accumulation of formaldehyde via maintaining DO at sufficient levels of 5–15%.When adopting this strategy, 1) DO was maintained at sufficient levels and thus the severe accumulation of formaldehyde was reduced to nearly zero level; 2) the methanol metabolic flux to cells maintenance could be kept at the lowest level (0.011 1/h vs 0.018–0.026 1/h); 3) monellin degradation by proteases was weakened; 4) the major energy regeneration pattern energizing monellin biosynthesis switched from formaldehyde (methanol) dissimilatory pathway to TCA cycle; 5) the maximum monellin expression titer of 2.45 g/L was obtained, which was 2.35–4.53 fold compared with that obtained using methanol-only feeding. In conclusion, the proposed on-line methanol/sorbitol co-feeding strategy could inhibit the severe accumulation of toxic metabolite formaldehyde through maintaining DO at the sufficient level and switching energy regeneration pattern from formaldehyde dissimilatory pathway to TCA cycle, while increasing cells metabolic activities reflected by a lower maintenance coefficient and formation rate of proteases etc., which eventually achieved an effective monellin expression in turn. Graphical abstract: Image 1 Highlights: A novel on-line feedback methanol/sorbitol co-feeding strategy was developed. The concentrations of methanol and DO were controlled at each sufficient level. The severe accumulation of formaldehyde was eliminated. The major energy regeneration pattern energizing monellin synthesis was switched. Monellin concentration reached the highest level of 2.45 g/L with this strategy.